Impacto da traça-verde Palpita vitrealis (Rossi) em diferentes cultivares de oliveira na Cova da Beira - Mateus, Helena (2012)
The attacks of jasmine moth were monitored in three olive cultivars, ‘Arbequina’, ‘Cobrançosa’ and ‘Galega Vulgar’, in a five years old olive grove and also in a plot of ‘Galega Vulgar’ one year old near Belmonte. The observations were carried out in 2000, from April 5 to November 7 and the first symptoms were observed on July 7. ‘Cobrançosa’ was significantly less attacked throughout the observation period and no significant differences were detected between the remaining. In order to explain these differences, leaf thickness of the different cultivars were compared by histological cuts but no differences were detected. No other differences regarding the presence and abundance of trichomes were found.